2014
DOI: 10.1111/mice.12074
|View full text |Cite
|
Sign up to set email alerts
|

A Grey System Theory‐Based Default Prediction Model for Construction Firms

Abstract: As the prediction of construction firm failure is of great importance for owners, contractors, investors, banks, insurance firms, and creditors, previous studies have developed several models for predicting the probability of construction firm default based on financial ratio analysis. However, to be applied, these models require a considerable quantity of data, including normally distributed data, and the models cannot tolerate too many changing factors. Furthermore, most of the approaches produce sample sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 64 publications
(108 reference statements)
0
16
0
Order By: Relevance
“…Therefore, the models for predicting business failure using data mining is actively proposed [1,2,[6][7][8][9]. However, previous studies have focused on short-term (within one year) prediction and have defined business failure based on legal events.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, the models for predicting business failure using data mining is actively proposed [1,2,[6][7][8][9]. However, previous studies have focused on short-term (within one year) prediction and have defined business failure based on legal events.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results showed that the proposed AdaBoost model outperforms other models. Cheng et al [8] and Tserng et al [9] proposed a model for predicting the default of construction companies within one year. They defined default as delisting due to bankruptcy, liquidation, or poor performance, as in Tserng et al [2].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The mentioned combination of ZOGP, ANP, and DEMATEL is applied for evaluating entrepreneurship policy of a company [170]. The latest applications analyze a variety of problems: measuring enterprises readiness for institutionalization [164], decision support for corporate social responsibility [165], examining organizational value cocreation [166], default prediction [181], and prioritizing risks [182]. In terms of methodology, Hashemkhani Zolfani et al [168] apply a hybrid of two rather novel methods, i.e.…”
Section: Hmcdm Applications In Industrial and Manufacturing Engineerimentioning
confidence: 99%